Polymer grafted smart mesoporous silica nanoparticles: challenges and advances in controlled drug delivery applications - Badiger, M. V.; Tiwari, N. (Nova Science Publishers, Inc., 2018)
The application of nanoparticles to intracellular drug delivery has attracted increasing attention in the last few decades. Among them, mesoporous silica nanoparticles (MSNs) have emerged as promising nanomaterials which have shown great potential towards incubation of both hydrophobic and hydrophilic drugs and their further internalization at the targeted site in physiological environment for the treatment of large number of diseases. Excellent properties of MSNs such as good stability control over morphology and tunable particle size and the pore structure gives them an edge over other organic or inorganic based nanoparticles. With these properties, there is a great scope in designing novel MSNs with functionalization at the surface as well as within the pores using biocompatible and biodegradable polymers, stimuli responsive groups, proteins etc. MSNs have shown great potential in biotechnological and biomedical applications. Efforts are also made to increase the biocompatibility and circulation time of drug loaded MSNs by coating various polymers onto the surface of MSNs. Extensive work on MSNs has been reported in the literature which is however scattered. In the present chapter, we have dealt with the advances made in MSNs as controlled and targeted drug delivery systems using either synthetic or natural polymers specifically towards cancer treatment.

Synthesis of hyaluronic acid hydrogels using click chemistry approach for biomedical applications - Gupta, N.; Tiwari, N.; Badiger, M. (Trends in carbohydrate research, 2018)
Hyaluronic acid (HA) is one of the most versatile biomaterial which forms an essential component of an extracellular matrix (ECM) and plays a vital role in wide variety of biological processes. Inherent biocompatibility, biodegradability and presence of functional groups for modification make it an attractive material for the synthesis of hydrogels for biological applications. In the present work, we have explored an azide-alkyne click chemistry approach for the preparation of HA hydrogels. Furthermore, we incorporated the hydrolysable carbonate ester linkages which are known to cleave in the physiological environment. The hydrogels with carbonate ester linkages and incubated with drug molecules can be used for the slow release of drug molecules. The hydrogels synthesized using azide alkyne click chemistry was characterized using NMR and IR spectroscopy.